The Problems of Students and Teachers in I'rab Learning at Islamic Boarding School - Zainul Arifin; Silva Namira; Munawir K; Engkizar Engkizar; Zainal Asril; Yunus Rahawarin; Japeri Japeri (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
I'rab learning is one of the aspects that must be studied by a student to help read the Yellow Book, but in fact, there was some student who have difficulty to the understanding I'rab, therefore, it is necessary to research to find out these problems. This research aims to identify whether the problems of students and teachers in this I'rab learning. This research uses a qualitative method with the case study type, data sources were taken to eight informants through direct interviews using a set of interview protocols. All the data were analyzed thematically using NVivo 12 Software. The research findings found nine main themes about the problems of students and teachers in I'rab learning. The nine themes consist of three problematic students themes: i) low vocabulary mastery (مفردات), ii) difficulty in I'rab sentences (جملة) in the Yellow Book, iii) lack of mastery of I'rab terms. Furthermore, the six teachers of problematic themes in I'rab learning include: iv) the teacher not teaching according to the ability of the students, v) less varied learning, vi) learning is only centered in one direction (Teacher Center), vii) teachers placement by expertise, viii) teachers changes frequently, and ix) mastering the concept of learning by the teacher was lacking. The results of this research can be used as preliminary data for future researchers in examining these problems in the context of different issues.